2016
DOI: 10.1002/14651858.cd010922.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy for people with autism spectrum disorder (ASD)

Abstract: To date, there is no evidence that hyperbaric oxygen therapy improves core symptoms and associated symptoms of ASD. It is important to note that adverse effects (minor-grade ear barotrauma events) can occur. Given the absence of evidence of effectiveness and the limited biological plausibility and possible adverse effects, the need for future RCTs of hyperbaric oxygen therapy must be carefully considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 88 publications
0
28
0
Order By: Relevance
“…Thus, we included 17 systematic reviews. 4,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Results from systematic reviews A summary of each systematic review is presented narratively below. In addition, Table 2 4,10-25 presents the issues addressed, the main findings from each systematic review and the quality of the evidence (based on the GRADE approach).…”
Section: Search Resultsmentioning
confidence: 99%
“…Thus, we included 17 systematic reviews. 4,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Results from systematic reviews A summary of each systematic review is presented narratively below. In addition, Table 2 4,10-25 presents the issues addressed, the main findings from each systematic review and the quality of the evidence (based on the GRADE approach).…”
Section: Search Resultsmentioning
confidence: 99%
“…Similarly, there is no of evidence supporting the benefits of hyperbaric oxygen therapy, and again this also has potentially serious adverse effects (Xiong et al, 2016). No evidence of benefits are found for secretin (Williams et al, 2012).…”
Section: Panel 4 Current Evidence Of Other Interventionsmentioning
confidence: 99%
“…Of the reviews that reported searching a website, 12 (31%) reported searching a type of website (eg, "the websites of relevant charities were searched") without specifying any examples of websites searched, which is insufficient detail for assessing or reproducing the searches, as the relevant websites cannot be identified. Of the 5 reviews that reported search terms or a narrative of how websites were navigated, Xiong et al 49 reported the most detailed narrative, stating that the interventions menu of ResearchAutism.net was browsed and the results under hyperbaric were downloaded. Other reviews stated that browsing was conducted without providing more detail and/or reported search terms.…”
Section: Additional Details Reported About Websitesmentioning
confidence: 99%